The Effects of Vitamin Supplementation on Drosophila Life Span Under Normoxia and Under Oxidative Stress - Sepehr Bahadorani; Peyman Bahadorani; J. P. Phillips; Arthur J. Hilliker (2008)
Vitamin A (retinol), vitamin C (ascorbic acid), and vitamin E (α-tocopherol) are each thought to play an important role in the aging process. Here, we investigated the effects of these vitamins on Drosophila melanogaster life span under different oxidative stress conditions. Among the vitamins tested, α-tocopherol exhibited the strongest antioxidant activity, extending average and maximum life span for wild-type flies under hyperoxia and for Cu/Zn superoxide dismutase-deficient (SOD1-deficient) flies under normoxia. Retinol supplementation extended life span of SOD1-deficient flies under normoxia, and ascorbic acid supplementation extended life span of wild-type flies under normoxia. However, both retinol and ascorbic acid exhibited a strong prooxidant activity under hyperoxia and shortened life span. Furthermore, ascorbic acid supplementation enhanced the toxic effects of iron, with the iron pool significantly increased in adult whole-body extracts. Taken together, our results document antioxidant and prooxidant contributions of vitamins to D. melanogaster life-span determination under normoxia and under oxidative stress.